Nargis: chothi jamaat k liye - Fouzia, Ehsan Farooqi (Karachi: Oxford university press, 2024)
Urdu ka Guldasta is a series of educational books, which are smelling the minds of both students and teachers from primary to eighth grade. Lessons and rhymes, exercises, engaging hands-on activities, creative writing, and easy-to-understand methods of teaching grammar and Learning make it different from other traditional textbooks,(which includes interesting and engaging books from Pre-Nursery to Class VIII).